INTEGRASI TEKNOLOGI DAN NILAI SYARIAH: ANALISIS UTAUT2 TERHADAP NIAT PENGGUNAAN MOBILE BANKING DI SAMARINDA - Seong, Majiid Ballo; Mainata, Dedy; Wibowo, Arista (Indonesian Scientific Journal of Islamic Finance, 2025)
Digital transformation in Islamic banking opens significant opportunities to improve efficiency, financial inclusion, and customer satisfaction. However, despite this progress, the adoption of Islamic mobile banking still lags behind that of conventional banks. This study aims to analyze several determinants influencing the intention to adopt Islamic mobile banking in Samarinda using the UTAUT2 theoretical framework. This study employed a quantitative approach, with 165 respondents selected through conventional sampling. Data collection used an online questionnaire, which was then processed using the SEM-PLS technique. Data analysis showed that habit, social influence, enabling conditions, hedonic motivation, price value, effort expectancy, and performance expectancy significantly influenced intention to use. Gender, age, and experience were shown to moderate some of the relationships between variables on intention to use. These findings provide a basis for developing digitalization strategies for Islamic banks that are more adaptive to consumer preferences.